Managerial and organizational challenges encountered in the development of sustainable technology: Analysis of Swedish biorefinery pilot and demonstration plants. (10th December 2020) - Mossberg, Johanna; Frishammar, Johan; Söderholm, Patrik; Hellsmark, Hans
Abstract: Pilot and demonstration plants (PDPs) perform critical tasks in the development of new sustainable technology by bridging basic knowledge generation and large-scale commercialization. Significant private and public funding has therefore been allocated to PDPs addressing climate change, pollution abatement technology and/or increased resource efficiency. After technology verification, PDPs typically struggle with evolving objectives, and reports of stalled or delayed development are common. Key problems may center on technical difficulties, but challenges of a non-technical nature are equally important, not least for the development of clean technology. This paper draws on a longitudinal case study of four PDPs used for advanced biorefinery technology development in Sweden and delineates the key managerial and organizational challenges that arise in and around such plants. By taking the actor networks around PDPs as the main unit of analysis, this paper gives a detailed description of various challenges, such as the division of responsibility for the operation and ownership of the PDPs, unclear roles and objectives, and the lack of specific competences and resources in the actor networks. One important conclusion is that improved knowledge about such challenges should increase the resilience of actor networks in and around PDPs, and also help shorten the formative phase of developing sustainable technology. Graphical abstract: Image 1 Highlights: Pilot and demonstration plants face key managerial and organizational challenges. Unclear responsibility for operation and ownership hampers development. Lack of specific competences/resources in the actor networks hampers development. Improved knowledge about key challenges increase resilience of the actor network.